Electronic Structure of GaAs and AlAs using a Hamiltonian Tight-Binding sp3s∗ (2021)
We calculate the electronic states in volume for GaAs and AlAs in Zinc-Blenda structure using the Tight-Binding (TB) method. The TB Hamiltonian was constructed using a base of s, p and s∗ orbitals. Thes∗ orbitals represent excited states with equal symmetry as the s orbitals. Carrying out the numericaldiagonalization of the Hamiltonian, the dispersion relationships were determined for some directions ofhigh symmetry of the first Brillouin zone (FBZ), obtaining a direct gap of 1.54 eV for GaAs and an indirectgap of 2.26 eV for AlAs. The total (DOS) and partial state densities indicate the presence of s orbitals inthe lower part of the valence band (BV), p orbitals in the upper part of the BV and in the lower part of theconduction band (BC), and s∗ orbitals on top of BC. Our results agree quite well with other experimentaland theoretical reports.